Legal mechanism of the tax on immovable property other than a land plot: directions of improvement with regard to foreign experience - Harkusha, V. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The relevance of the research topic is due to the need to find ways to reform local taxes and fees with a view to enhancing their fiscal impact on the revenue side of local self-government budgets. Thus, the author identifies the features of the tax on immovable property other than a land plot, in particular: a) the tax is local and is imposed by the authorities of a village, town or city at their discretion; b) the tax is direct, since the real and actual payer coincide; c) given the object of taxation, it is a property tax. As rightly noted by scholars, the tax on immovable property other than a land plot is characterised by the stability of revenues to the budgets of villages, towns and cities, and in accordance with the provisions of the Budget Code of Ukraine, the funds from the tax under study in this article are received by the respective budgets in full. The article examines the elements of the legal mechanism of tax on immovable property other than a land plot. Using the example of the decision of the Administrative Court of Cassation dated 5 February 2025 in case No. 500/6132/23, the author highlights the problematic issue of whether non-residential real estate can be classified as a taxable property in case of leasing part of such real estate for free use. Using the example of the budget of the Lviv city territorial community, the author traces the dynamics of revenues to the relevant budget during 2021-2024. It is established that the tax on immovable property other than a land plot does not have a significant impact on the budget revenues, and the dynamics of revenues shows that the trend of revenues from the collection of this tax is not increasing, but is stable. Therefore, it is imperative to review the existing elements of the legal mechanism of the tax in order to find the best ways to improve it further. Based on the example of the study of real estate taxation in foreign countries, the author determines that only a few countries use the area as the basis for real estate taxation, which in turn has both advantages in terms of ease of tax administration and disadvantages, since it does not take into account the characteristics of the taxable object, such as: a) the condition of the taxable object; b) the year of construction; c) the value of residential and non-residential real estate subject to taxation.